Scripture, the Genesis of Doctrine: Doctrine and Scripture in Early Christianity, vol 1 - Young, Frances M. (Eerdmans, 2023)
Intro -- Title Page -- Copyright -- Dedication -- Contents -- Foreword by David F. Ford -- Preface -- List of Abbreviations -- 1. Doctrine and Scripture: Mutually Coinherent? What Are the Problems? -- 1. A Widening Gap? -- 2. The Developmental Model -- 3. Hellenization of the Gospel -- 4. Changed Perspectives -- 2. Rethinking the Context: The School-Like Character of Early Christian Groups -- 1. Christianity: A Religion or What? -- 2. Synagogues and Schools -- 3. The Sociological Turn -- 4. Schools within "Fractionated" Churches: Two Key Examples -- 4.1. Rome in the Second Century -- 4.2. Alexandria in the Second and Early Third Centuries -- 5. Hellenization or the Acculturation of a Distinct Identity? -- 5.1. Acculturation as a Network of Schools -- 5.2. A School with a Distinct Identity? -- 6. Conclusion and Prospect -- 3. Reading Texts, Asking Questions: Key Second-Century Conclusions -- 1. Scripture and Its Exegesis -- 1.1. Marcion's Biblical Criticism and Its Context -- 1.2. Ptolemaeus's Letter to Flora -- 1.3. Justin's Reading of Scripture -- 2. God and Creation -- 2.1. Marcion and the God of the Scriptures -- 2.2. Marcion's Good God and the God of the Beyond -- 2.3. From Marcion's Duality to God's Monarchia -- 3. Conclusion -- 4. Summing up Scripture: From Gospel of Truth to Canon of Truth -- 1. Gnosticism -- 1.1. The Gospel of Truth -- 1.1.1. Overview -- 1.1.2. Saving the Lost: Gospel of Truth 31-34 -- 1.1.3. Jesus as Revealer: Gospel of Truth 18.7-20.2 and 30.35-31.35 -- 1.1.4. Names in the Book of the Living: Gospel of Truth 19.34-23.31 and 37.35-43.22 -- 1.2. Behind and Beyond the Gospel of Truth -- 1.2.1. The Gospel of Truth and the Valentinian System -- 1.2.2. The Gospel of Truth and Scripture -- 2. The Canon of Truth -- 2.1. Irenaeus's Demonstration of the Apostolic Preaching and the Rule of Faith -- 2.2. Proof from Prophecy.